AB0208 Reduced Hand Function Indicates Higher Disease Activity In Patients With Rheumatoid And Psoriatic Arthritis - Coppers, Birte; Heinrich, Simon; Bayat, Sara; Tascilar, Koray; Kleyer, Arnd; Simon, David; Minopoulou, Ioanna; Corte, Giulia; Fagni, Filippo; Schönau, Verena; Bohr, Daniela; Leyendecker, Sigrid; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Measuring disease activity in patients with inflammatory arthritis remains challenging and is mainly based on physician-dependent assessments, subjective measures and just one blood biomarker of inflammation with no indication of the subclinical or functional state of the patients [1, 2]. Patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA) present with impaired hand function compared to healthy controls [3, 4]. While hand function is well studied in RA patients [5], data is sparse for PsA patients. Objectives: To employ the association between clinical disease activity scores and objectively measured hand function impairment in RA and PsA patients. Methods: Three conventional hand function tests were performed by PsA (CASPAR criteria) and RA (ACR/EULAR 2010 criteria) patients (Internal Medicine 3 outpatient clinics Erlangen, Germany) and healthy controls (HC) (study: Ethics #357_20B, DRKS00032490). The clinically assessed disease activity scores (Disease Activity in Psoriatic Arthritis Score (DAPSA) [1], Disease Activity Score 28 (DAS28) [2]) and the best trial for each of the hand function tests were used for this analysis: the highest out of three trials for an isometric grip strength test (Dynamometer, Saehan, Korea, Figure 1 A), the highest out of two trials for a dynamic grip strength test (Martin Vigorimeter, Germany, Figure 1 B) and the fastest out of two trials for the fine motor skill Moberg Picking-Up Test (MPUT) (Figure 1 C) for each hand. Mixed-effect linear regression models adjusted for age were used to employ the associations between the clinical disease activity scores and hand function tests of the patients. Analyses were stratified by sex. Results: We included 76 PsA patients (37 male, 52.0±4.3 years; DAPSA: 10.2±7.1), 73 RA patients (24 male, 53.9±14.1 years; DAS28: 2.6±0.9), and 77 HC (37 male, 46.0±18.5 years) in this study. For RA patients one-unit increase of the DAS28 was significantly associated with reduced dynamic grip strength for both sexes (Table 1, p<0.05) but not with a reduced isometric grip strength. Performance time of the MPUT was on average 11% (male) and 7% (female) longer with one-unit increase in the DAS28 score, but was not statistically significant. In PsA patients, a one-unit increase in the DAPSA score was associated with worse hand function on all measurements, but these were significant only in male patients (all p<0.05, Table 1). The MPUT showed worse performance of 2% in males and 1% in females for each one-point increase of the DAPSA score. Conclusion: Increased disease activity is associated with reduced hand function in PsA and RA patients. The dynamic grip strength test (vigorimeter) seems to be more sensitive than the isometric grip strength test (dynamometer) to detect functional changes in relation to disease activity. For male PsA patients, the fine motor MPUT may be particularly suitable to reflect changes in disease activity. Longitudinal properties of these measurements, such as sensitivity to change, need to be further explored. An overall low disease activity in PsA and RA patients is a limitation of our stud

Author Correction: DeepNAPSI multi-reader nail psoriasis prediction using deep learning. - Folle, Lukas; Fenzl, Pauline; Fagni, Filippo; Thies, Mareike; Christlein, Vincent; Meder, Christine; Simon, David; Minopoulou, Ioanna; Sticherling, Michael; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Scientific Reports, 2023)
EVALuna2:538275

Baricitinib Improves Bone Properties and Biomechanics in Patients With Rheumatoid Arthritis: Results of the Prospective Interventional BARE BONE Trial - Simon, David; Minopoulou, Ioanna; Kemenes, Stephan; Bayat, Sara; Tascilar, Koray; Mutlu, Melek Yalcin; Valor-Méndez, Larissa; Krönke, Gerhard; Hueber, Axel J.; Schett, Georg; Kleyer, Arnd (Arthritis and Rheumatology, 2023)
Objective: Rheumatoid arthritis (RA) is characterized by erosive joint damage, deterioration of bone mass, and biomechanics. Preclinical evidence suggests a beneficial effect of Janus kinase inhibition (JAKi) on bone properties, but clinical data are scarce to date. In this study, we evaluated the effect of JAKi through baricitinib (BARI) on 1) volumetric bone mineral density (vBMD), bone microstructure, biomechanics, and erosion repair and 2) synovial inflammation in RA patients. Methods: Prospective, single-arm, interventional, open-label, single-center phase 4 study in RA patients with pathological bone status and clinical indication of JAKi (BARE BONE trial). Participants received BARI (4 mg/day) over 52 weeks. To assess bone properties and synovial inflammation, high-resolution computed tomography scans and magnetic resonance imaging were performed at baseline (BL), week 24, and week 52. Clinical response and safety were monitored. Results: Thirty RA patients were included. BARI significantly improved disease activity (Disease Activity Score in 28 joints using the erythrocyte sedimentation rate: 4.82 ± 0.90 to 2.71 ± 0.83) and synovial inflammation (RAMRIS synovitis score: 5.3 [4.2] to 2.7 [3.5]). We observed a significant improvement in trabecular vBMD with a mean change of 6.11 mgHA/mm3 (95% confidence interval [95% CI] 0.01–12.26). Biomechanical properties also improved with mean change from baseline in estimated stiffness of 2.28 kN/mm (95% CI 0.30–4.25) and estimated failure load of 98.8 N (95% CI 15.9–181.7). The number and size of erosions in the metacarpal joints remained stable. No new safety signals with BARI treatment were observed. Conclusion: Bones of RA patients improve with BARI therapy, as shown by an increase in trabecular bone mass and an improvement of biomechanical properties.
CRIS-Team Scopus Importer:2023-09-29

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

Fibroblast Activation in Psoriasis Patients Assessed by Ga-68-FAPI-04 PET-CT Is Associated with Progression to Psoriatic Arthritis - Fagni, Filippo; Simon, David; Kleyer, Arnd; Tascilar, Koray; Taubmann, Jule; Bayat, Sara; Minopoulou, Ioanna; Mutlu, Melek Yalcin; Atzinger, Armin; Kuwert, Torsten; Schett, Georg; Schmidkonz, Christian (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Fully Human Anti-CD19 CAR T Cells Derived from Systemic Lupus Erythematosus Patients Exhibit Cytotoxicity with Reduced Inflammatory Cytokine Production - Dingfelder, Janin; Aigner, Michael; Taubmann, Jule; Minopoulou, Ioanna; Park, Soo; Kaplan, Charles D.; Cheng, Joseph K.; Van Blarcom, Tom; Schett, Georg; Mackensen, Andreas; Lutzny-Geier, Gloria (Transplantation and Cellular Therapy, 2024)
KYV-101 is an autologous anti-CD19 chimeric antigen receptor (CAR)-T cell therapy under investigation for patients with B-cell driven autoimmune diseases. Hu19-CD828Z is a fully human anti-CD19 CAR designed and demonstrated to have a favorable clinical safety profile. Since anti-CD19 CAR T cells target and kill B cells in both circulation and tissues, the treatment with Hu19-CD828Z CAR T cells offers great potential in depleting autoreactive B cells. Demonstrate that Hu19-CD828Z CAR T cells manufactured from cryopreserved leukaphereses from patients with systemic lupus erythematosus (SLE) exhibit CAR-mediated and CD19-dependent cytokine release, proliferation and cytotoxicity when co-cultured with autologous primary B cells. T cells were enriched from cryopreserved leukaphereses from SLE patients or healthy donors (HD). CAR T cells were generated by transducing these cells with a lentiviral vector encoding Hu19-CD828Z. CAR-mediated and CD19-dependent activity was monitored in vitro in a set of cytotoxicity, cytokine release, and proliferation studies, in response to autologous primary CD19+ B cells, a CD19+ cell line (NALM-6), or a CD19− cell line (U937). Hu19-CD828Z CAR T cells produced from SLE patients or HD induced greater proliferation and dose-dependent cytotoxicity against both autologous primary B cells and the CD19+ NALM-6 cells than nontransduced control T cells or co-cultures with a CD19− cell line. Interestingly, there was lower inflammatory cytokine production from SLE patient-derived CAR T cells compared to HD donor-derived CAR T cells with either CD19+ cells or primary B cells. Hu19-CD828Z CAR T cells generated from SLE patient lymphocytes demonstrate CAR-mediated and CD19-dependent activity against autologous primary B cells with reduced inflammatory cytokine production supporting KYV-101 as a novel potential therapy for the depletion of pathogenic B cells in SLE patients.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Chimeric antigen receptor; Cytokines; Systemic Lupus Erythematosus

IL-1 Inhibitors in the Treatment of Familial Mediterranean Fever: Treatment Indications and Clinical Features in a Large Real-World Cohort - Yalcin-Mutlu, Melek; Icacan, Ozan Cemal; Yildirim, Fatih; Temiz, Selahattin Alp; Fagni, Filippo; Schett, Georg; Tascilar, Koray; Minopoulou, Ioanna; Burul, Gokhan; Bes, Cemal (Journal of Clinical Medicine, 2024)
Background: The accruing evidence about the efficacy of anti-IL-1 agents in Familial Mediterranean Fever (FMF) patients led to their widespread off-label use. Therefore, identifying precise indications and clinical characteristics of IL-1i-warranting patients are important. This study investigated the clinical characteristics and treatment indications of patients with FMF requiring interleukin 1 inhibition therapy (IL-1i). Methods: Hospital records of FMF patients attending a tertiary care center at the Department of Rheumatology, University of Health Sciences, Basaksehir Cam and Sakura City Hospital were retrospectively analyzed. Data on symptoms and disease manifestations, age of symptom onset, time to diagnosis, MEFV variants, type of treatment, and their indications were collected. Results: Between June 2020 and March 2023, 312 FMF patients were identified. The mean age at the onset of symptoms was 14.0, and the mean time to diagnosis was 11.9 years. In total, 87.1% of patients were receiving colchicine monotherapy, while the remaining 11.8% warranted IL-1i. Clinical symptoms and flare manifestations did not show a significant difference between the two groups. However, patients receiving IL-1i started having symptoms at younger age (11.5 vs. 14.5, p = 0.042) and time to diagnosis was longer (18.2 vs. 11.0, p < 0.01). M694V homozygosity was more common in patients receiving IL-1i. Indications for patients receiving IL-1i were colchicine resistance (8.0%), secondary amyloidosis (5.1%), and colchicine intolerance (2.2%). Conclusions: This study shows that a subset of FMF patients, particularly those with a more severe phenotype with an earlier disease onset and M694V homozygosity, require IL-1i treatment despite the overall good efficacy and tolerability of colchicine, primarily due to colchicine resistance, intolerance, or complications such as amyloidosis.
CRIS-Team Scopus Importer:2024-07-12
Keywords: amyloidosis; colchicine intolerance; colchicine resistance; familial mediterranean fever; interleukin-1 inhibitors

Imaging in inflammatory arthritis: progress towards precision medicine - Minopoulou, Ioanna; Kleyer, Arnd; Yalcin-Mutlu, Melek; Fagni, Filippo; Kemenes, Stephan; Schmidkonz, Christian; Atzinger, Armin; Pachowsky, Milena; Engel, Klaus; Folle, Lukas; Roemer, Frank; Waldner, Maximilian; et al. (Nature Reviews Rheumatology, 2023)
Imaging techniques such as ultrasonography and MRI have gained ground in the diagnosis and management of inflammatory arthritis, as these imaging modalities allow a sensitive assessment of musculoskeletal inflammation and damage. However, these techniques cannot discriminate between disease subsets and are currently unable to deliver an accurate prediction of disease progression and therapeutic response in individual patients. This major shortcoming of today’s technology hinders a targeted and personalized patient management approach. Technological advances in the areas of high-resolution imaging (for example, high-resolution peripheral quantitative computed tomography and ultra-high field MRI), functional and molecular-based imaging (such as chemical exchange saturation transfer MRI, positron emission tomography, fluorescence optical imaging, optoacoustic imaging and contrast-enhanced ultrasonography) and artificial intelligence-based data analysis could help to tackle these challenges. These new imaging approaches offer detailed anatomical delineation and an in vivo and non-invasive evaluation of the immunometabolic status of inflammatory reactions, thereby facilitating an in-depth characterization of inflammation. By means of these developments, the aim of earlier diagnosis, enhanced monitoring and, ultimately, a personalized treatment strategy looms closer.
CRIS-Team Scopus Importer:2023-09-29

Intensity and longevity of SARS-CoV-2 vaccination response in patients with immune-mediated inflammatory disease: a prospective cohort study. - Simon, David; Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Taubmann, Jule; Mutlu, Melek Yalcin; Knitza, Johannes; et al. (The Lancet Rheumatology, 2022)
Background: Concerns have been raised about the reduced immunogenicity of vaccines against SARS-CoV-2 in patients with immune-mediated inflammatory diseases and the higher risk of breakthrough infections. The objective of our study was to investigate the intensity and longevity of SARS-CoV-2 vaccination responses in patients with immune-mediated inflammatory diseases, and to assess the effects of diagnosis, treatment, and adapted vaccination schedules. Methods: SARS-CoV-2 IgG antibody response after SARS-CoV-2 vaccination was measured over time in a large prospective cohort of healthy controls and participants with immune-mediated inflammatory diseases (attending or admitted to affiliated centres) between Dec 15, 2020, and Dec 1, 2021. Cohort participants with immune-mediated inflammatory diseases and control participants with no diagnosis of immune-mediated inflammatory diseases, were eligible for this analysis. Demographic data and disease-specific data were collected using a questionnaire. Humoral response was compared across treatment and disease groups, and with respect to the receipt of additional vaccinations. SARS-CoV-2 antibody response was measured by ELISA using optical density ratio units and modelled over time with age and sex adjustment using mixed-effects models. Using these models, marginal mean antibody titres and marginal risks of a poor response (optical density ratio <1·1) were calculated for each week starting from week 8 after the first vaccination to week 40. Findings: Among 5076 individuals registered, 2535 participants with immune-mediated inflammatory diseases (mean age 55·0 [15·2] years; 1494 [58·9%] women and 1041 [41·1%] men) and 1198 healthy controls (mean age 40·7 [13·5] years; 554 [46·2%] women and 644 [53·8%] men) were included in this analysis. Mean antibody titres were higher in healthy controls compared with people with immune-mediated inflammatory diseases at all timepoints, with a peak antibody response in healthy controls (mean optical density ratio 12·48; 95% CI 11·50-13·53) of more than twice that in participants with immune-mediated inflammatory diseases (5·50; 5·23-5·77; mean difference 6·98; 5·92-8·04). A poor response to vaccination was observed in participants with immune-mediated inflammatory diseases who were taking B-cell inhibitors (peak mean difference from healthy controls 11·68; 10·07-13·29) and T-cell inhibitors (peakmean difference from healthy controls 10·43; 8·33-12·53). Mean differences in antibody responses between different immune-mediated inflammatory diseases were small. Participants with immune-mediated inflammatory diseases who were given a third vaccine dose had higher mean antibody titres than did healthy controls vaccinated with two vaccine doses at 40 weeks after the initial vaccination (mean difference 1·34; 0·01-2·69). Interpretation: People with immune-mediated inflammatory diseases show a lower and less durable SARS-CoV-2 vaccination response and are at risk of losing humoral immune protection. Adjusted vaccination schedules with earlier booster doses or more frequent re-doses, or both, could better protect people with immune-mediated inflammatory diseases. Funding: Deutsche Forschungsgemeinschaft, Bundesministerium für Bildung und Forschung, European Research Council, Innovative Medicine Initiative, Friedrich-Alexander-Universität Erlangen-Nürnberg, Else Kröner-Memorial Foundation.
EVALuna2:506737

Metabolic and molecular imaging in inflammatory arthritis - Noversa de Sousa, Rita; Tascilar, Koray; Corte, Giulia; Atzinger, Armin; Minopoulou, Ioanna; Ohrndorf, Sarah; Waldner, Maximilian; Schmidkonz, Christian; Kuwert, Torsten; Knieling, Ferdinand; Kleyer, Arnd; Ramming, Andreas; et al. (RMD Open, 2024)
It is known that metabolic shifts and tissue remodelling precede the development of visible inflammation and structural organ damage in inflammatory rheumatic diseases such as the inflammatory arthritides. As such, visualising and measuring metabolic tissue activity could be useful to identify biomarkers of disease activity already in a very early phase. Recent advances in imaging have led to the development of so-called ‘metabolic imaging’ tools that can detect these changes in metabolism in an increasingly accurate manner and non-invasively. Nuclear imaging techniques such as 18F-D-glucose and fibroblast activation protein inhibitor-labelled positron emission tomography are increasingly used and have yielded impressing results in the visualisation (including whole-body staging) of inflammatory changes in both early and established arthritis. Furthermore, optical imaging-based bedside techniques such as multispectral optoacoustic tomography and fluorescence optical imaging are advancing our understanding of arthritis by identifying intra-articular metabolic changes that correlate with the onset of inflammation with high precision and without the need of ionising radiation. Metabolic imaging holds great potential for improving the management of patients with inflammatory arthritis by contributing to early disease interception and improving diagnostic accuracy, thereby paving the way for a more personalised approach to therapy strategies including preventive strategies. In this narrative review, we discuss state-of-the-art metabolic imaging methods used in the assessment of arthritis and inflammation, and we advocate for more extensive research endeavours to elucidate their full field of application in rheumatology.
CRIS-Team Scopus Importer:2024-02-23

Real-World-Evidence of Digital Health Applications (DiGAs) in Rheumatology: Insights from the DiGAReal Registry - Albrecht, Alexander; Taubmann, Jule; Minopoulou, Ioanna; Hatscher, Lukas; Kleinert, Stefan; Mühlensiepen, Felix; Welcker, Martin; Leipe, Jan; Schulz, Nils; Klemm, Philipp; Hueber, Axel; Schett, Georg; et al. (Rheumatology and Therapy, 2025)
Introduction: Prescribable digital health applications (DiGAs) present scalable solutions to improve patient self-management in rheumatology, however real-world evidence is scarce. Therefore, we aimed to assess the effectiveness, usage, and usability of DiGAs prescribed by rheumatologists, as well as patient satisfaction. Methods: The DiGAReal registry includes adult patients with rheumatic conditions who received a DiGA prescription. Data at baseline (T0) and the 3-month follow-up (T1) were collected through electronic questionnaires. Study outcomes included DiGA-specific outcome assessments as well as generic outcome assessments, including the Patient Global Impression of Change (PGIC), Patient Activation Measure (PAM®), and the German Telehealth Usability and Utility Short Questionnaire (TUUSQ). Changes between T0 and T1 were analyzed using descriptive statistics and paired tests. Results: A total of 191 patients were included between June 2022 and April 2023. Of these, 127 completed the 3-month follow-up, and 114 reported using the prescribed DiGA, with 66% reporting weekly use and 15% completing the full DiGA program. The most commonly prescribed DiGAs targeted pain management (53%). Symptom improvement was reported by 51% of patients using a DiGA, with significant reductions in exhaustion levels (p = 0.03). Significant DiGA-specific improvements were observed for DiGAs addressing back pain (p = 0.05) and insomnia (p = 0.006). However, no overall significant changes were detected in patient activation, health literacy, pain, overall health, or disease activity. Back pain and weight management DiGAs were the most effective, frequently used, and best-rated DiGAs, with symptom improvements reported by 50% to 82% of patients. Conclusion: The findings suggest that DiGAs can improve symptom management in rheumatic patients, especially for conditions like back pain and weight control. Further real-world evidence is needed and may support value-based digital health efforts and reimbursement frameworks.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Digital health applications; Digital therapeutics; Patient self-management; Real-world evidence; Rheumatology

Tixagevimab/cilgavimab for the prevention of COVID-19 in vaccine-refractory patients with autoimmune diseases: a prospective cohort study. - Minopoulou, Ioanna; Tascilar, Koray; Corte, Giulia; Mutlu, Melek Yalcin; Schmidt, Katja; Bohr, Daniela; Hartmann, Fabian; Manger, Karin; Manger, Bernhard; Korn, Klaus; Kleyer, Arnd; Simon, David; et al. (Rheumatology, 2024)
OBJECTIVES: To investigate the effects of passive immunization with the anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) monoclonal antibodies tixagevimab/cilgavimab on humoral responses and on coronavirus disease 2019 (COVID-19) outcomes in vaccine-refractory patients with immune-mediated inflammatory diseases (IMIDs) at high risk of severe COVID-19. METHODS: A prospective cohort study was performed on a cohort of high-risk vaccine-refractory IMID patients treated with a single dose of tixagevimab/cilgavimab (150 mg/150 mg). COVID-19 outcomes as well as serum and salivary anti-SARS-CoV-2 IgG were assessed at baseline and for at least 6 months. Results were compared with an untreated high-risk vaccine-refractory IMID population. Standardized incidence ratios (SIRs) of COVID-19 compared with the general population were calculated for both groups. RESULTS: A total of 38 high-risk IMID patients received tixagevimab/cilgavimab and were compared with 114 untreated high-risk IMID controls. Serum anti-spike IgG increased to 6.6 OD (s.d. 0.8) at day 1 and remained positive up to month 6 [6.3 OD (s.d. 1.4)]. Salivary anti-spike IgG peaked at month 2 [1.6 OD (s.d. 1.1)] and decreased from month 3 [0.8 OD (s.d. 0.3)]. No severe or extended infection was observed in the tixagevimab/cilgavimab group. Compared with the general population, the SIR of COVID-19 in treated patients was 0.76 (95% CI 0.24, 1.58) despite the increased risk profile. The SIR of the control group was 1.51 (95% CI 1.07, 2.02), corresponding to a significantly increased incidence. CONCLUSIONS: Passive immunization with tixagevimab/cilgavimab is safe and effective in inducing anti-SARS-CoV-2 immunity and potentially in preventing COVID-19 in high-risk vaccine-refractory IMID patients. These data provide a proof of concept for the use of monoclonal antibodies as a preventative strategy against SARS-CoV-2 in vulnerable populations.
EVALuna2:540332

Von der konventionellen Bildgebung zum Cutting Edge Imaging in der Rheumatologie - Simon, David; Kemenes, Stephan; Minopoulou, Ioanna; Kleyer, Arnd (Zeitschrift für Rheumatologie, 2023)
Imaging instruments, such as conventional X‑ray, ultrasound and magnetic resonance imaging (MRI) are now fully established and highly valued in the care of rheumatology patients. However, the information provided by these imaging modalities in their current form is of limited utility for the prognostic prediction of individual patient outcomes. This article illuminates an important part of the development of imaging and shows that the vision of personalized medicine is becoming increasingly more tangible due to the further development of high-resolution imaging techniques, molecular imaging and artificial intelligence.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Artificial intelligence; Magnetic resonance imaging; Molecular imaging; Personalized medicine; Sonography